The risk for delayed development in low birth weight, appropriate for gestational age preterm infants - Stanza Uga Peryoga; Abdurachman Sukadi; Sambas Wiradisuria (Paediatrica Indonesiana, 2005)
Background Preterm infants, particularly those who have hadsevere asphyxia, hyperbilirubinemia, and sepsis, tend to be at riskfor neurodevelopmental impairment.Objective The purpose of this study was to assess the risk for de-layed development in low birth weight (LBW), appropriate for gesta-tional age (AGA) preterm infants compared to that in term, non-LBWinfants, and to investigate the roles of severe asphyxia, sepsis, andhyperbilirubinemia as potential risk factors for delayed development.Methods This was a hospital-based retrospective cohort studyinvolving preterm, LBW and term, non-LBW infants conducted inHasan Sadikin Hospital, Bandung. The Bayley InfantNeurodevelopmental Screener (BINS) test was performed to as-sess the risk of delayed development at 3 months of corrected agefor the preterm infants and at 3 months of chronological age for theterm infants. Bivariate analysis using the chi-square test and mul-tivariate analysis using logistic regression were performed.Results One hundred and twelve infants fulfilled eligibility criteria,consisting of 52 preterm, LBW and 60 term, non-LBW infants. Basedon the BINS test, of the preterm, LBW infants, 32 (61%) were atlow risk, 11 (21%) at moderate risk, and 9 (17%) at high risk fordelayed development. Of the control infants, 49 (82%) were at lowrisk, 10 (17%) at moderate risk, and 1 (1.7%) at high risk for de-layed development. Logistic regression analysis showed signifi-cant association between accompanying diseases such as sepsis(OR=25.60; P=0.001) and hyperbilirubinemia (OR=16.07; P=0.001)with delayed development. Despite more than twofold odds fordelayed development in infants with severe asphyxia (OR=2.51)and LBW-prematurity (OR=2.47), the association was statisticallyinsignificant (P=0.20 and P=0.15, respectively).Conclusions In preterm infants appropriate for gestational age,prematurity and low birth weight alone may or may not predisposeto delayed development at 3 months of age. However, the risk fordelayed development in such infants is increased when sepsis orhyperbilirubinemia is present